Teaching profiles and their relationship to perceptions of student learning of generic skills in the Hungarian higher education context - Bendeliani, Natia; Tuononen, Tarja (Journal of University Teaching and Learning Practice, 2026)
Teachers’ approaches to teaching, which are understood as the interplay between their intentions in a given teaching situation and the strategies they employ, have been widely examined in higher education research. However, this concept has not been sufficiently studied in relation to teaching generic skills, despite universities increasingly recognising their importance. Addressing this gap in the present study, we examined higher education teachers’ approaches to teaching and their perceptions of student learning of generic skills. Conducted in the Hungarian higher education context, where research on teaching generic skills remains scarce, the study provides novel insights. A total of 221 university teachers filled in the online questionnaire. The data were analysed using Pearson’s correlations, cluster analysis, the Chi-square test, and a one-way ANOVA. Three distinct teaching profiles emerged: interactive-organised, transmissive, and mixed. These profiles were associated with different perceptions of how students develop generic skills such as critical thinking, collaboration, multidisciplinary skills, and self-regulation. Disciplinary background also played a role in shaping profile distribution. Overall, the findings provide context-sensitive insights into how teaching approaches influence perceptions of generic-skill learning and extend the validity of the instrument in a cross-national context.